Epidemiology of concomitant injuries in traumatic thoracic aortic rupture: A meta-analysis. (December 2014) - Antonopoulos, Constantine N; Sfyroeras, George S; Kallinis, Aristides; Kakisis, John D; Liapis, Christos D; Petridou, Eleni Th
Traumatic thoracic aortic rupture is a highly lethal injury. For those who arrive alive at the hospital, it is of utmost importance to quickly evaluate concomitant injuries and prioritize therapeutic interventions. We aimed to review the frequency of concomitant injuries in patients with thoracic aortic rupture, according to anatomic location and type of injury. A systematic literature search of six medical databases led to the identification of 90 publications; 27 categories of thoracic aortic rupture concomitant injuries were thereafter created. The respective pooled proportions and 95% confidence intervals were calculated and ranked in order of frequency. Among the 7258 patients studied, orthopedic fractures were the most frequent thoracic aortic rupture concomitant injury, amounting to a high pooled proportion of almost 70%, followed by thoracic injury in ∼50% and abdominal injury in over 40%. Pooled proportion for any type of head injury was also high (37%) pointing to the multiple-injury type of lesions among thoracic aortic rupture victims. Thoracic aortic rupture is a devastating injury, but rarely occurs as a sole traumatic entity. The recognition of concomitant thoracic, abdominal, head injuries and fractures after thoracic aortic rupture is of paramount importance. Future studies should focus on the impact of these injuries upon survival, morbidity and disability of multiple-injured thoracic aortic rupture patients.